ANXIOLYTIC - LIKE PROPERTIES OF HALLEA CILIATA IN MICE - Jacqueline Stephanie, Njapdounke Kameni; Gisele, Nkantchoua Nkamguie; Fleur Clarisse, Moto Okomolo; Germain, aiwe Sotoing; Neteydji, idiki; Simon, Pale; Espoir Rigobert, Ayissi Mbomo; Elisabeth, Ngo Bum (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of the present study was to evaluate the anxiolytic properties of the decoction of stem bark of Hallea ciliatain mice. The decoction of Hallea ciliata is used in traditional medicine in Cameroon to treat diseases like anxiety disorders, fever,infantile convulsions and malaria.Materials and Methods: Stress induced hyperthermia, elevated plus maze, open field and hole-board tests were used. Four differentdoses of the decoction were administered to mice and their effects were compared to the effects of diazepam and vehicle.Phytochemical characterization of the decoction revealed the presence of alkaloids, flavonoids, tannins and saponins.Results: Administration of Hallea ciliata resulted in a significant decrease of stress induced hyperthermia in mice at the doses of29.5, 59 and 118 mg/kg. In the elevated plus maze test, Hallea ciliata increased the number of entries and the percentages of entriesand time into the open arms, and reduced the number of entries and the percentages of entries and time into the closed arms. In thehole-board test, Hallea ciliata increased the number of both head-dipping and crossing and decreased the latency to the first headdipsand rearing. The decoction of Hallea ciliata and diazepam increased locomotion in the open field test.Conclusion: The number of rearing and the mass of fecal boli produced were decreased in mice treated with decoction anddiazepam. In conclusion, the results indicated that decoction of Hallea ciliata has anxiolytic-like properties in mice and couldpotentially be used for anxiety treatment.